2015
DOI: 10.1063/1.4918481
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cavity pressure and warpage of polyoxymethylene thin walled injection molded parts: Experiments and simulations

Abstract: Influence of mold surface temperature on polymer part warpage in rapid heat cycle molding AIP Conference Proceedings 1593, 189 (2014) Abstract. Process analysis and simulations on molding experiments of 3D thin shell parts have been conducted. Moldings were carried out with polyoxymethylene (POM). The moldings were performed with cavity pressure sensors in order to compare experimental process results with simulations. The warpage was characterized by measuring distances using a tactile coordinate measuring ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The first verification of the timings without induction heating showed that both ram acceleration and using machine geometry as hot runner to get the effect of all the compressible material were needed to obtain such accurate results, as demonstrated in [41,42]. This was transferred to the flow simulation together with transient thermal results of the induction heating, and these showed the same trends as in the experiments.…”
Section: Resultsmentioning
confidence: 89%
“…The first verification of the timings without induction heating showed that both ram acceleration and using machine geometry as hot runner to get the effect of all the compressible material were needed to obtain such accurate results, as demonstrated in [41,42]. This was transferred to the flow simulation together with transient thermal results of the induction heating, and these showed the same trends as in the experiments.…”
Section: Resultsmentioning
confidence: 89%
“…Pressure dependent viscosity has proved to have an effect on the filling pressure required, and the packing pressure levels. This is shown by Pantani et al [12] and Guerrier et al [14] to give a higher pressure drop through the melt, giving more realistic pressure predictions. The D3 coefficient from Eq.…”
Section: Pressure Dependent Viscositymentioning
confidence: 80%
“…This will be referred to as the reference simulation, and this was implemented with the mentioned ram speed, the temperatures and the different (packing, cooling) times specified in the experimental setup. The size and the geometry of the cushion in front of the sprue and up to the nozzle can have a significant impact on the filling simulation of the cavity and must be taken into account [12][13] [14]. This is of particular importance when the volume of the cushion is larger than the runner/cavity system to be molded.…”
Section: Setup Of Initial and Improved Simulationsmentioning
confidence: 99%
“…Tentunya diperlukan teknologi yang cukup baik dari segi mesin injeksi, injection molding, material, prosedur, dan personel agar dapat menghasilkan produk plastik sesuai dengan yang kita inginkan. Menggunakan pendorong, bahan termoplastik yang meleleh dipompa ke dalam cetakan berpendingin air selama proses pencetakan injeksi, menyebabkannya mengeras (Guerrier et al, 2015). Setting parameter pada mesin injection moulding merupakan salah satu elemen kunci diantara sekian banyak parameter tersebut.…”
Section: Pendahuluanunclassified